EVALUATING TECHNOLOGY ADOPTION RELEVANCE IN AUDIT AND NON-AUDIT FIRMS: A COMPARATIVE ANALYSIS - Adriana Shamsudin; Mohd Noor Azli Ali Khan; Ahmad Jusoh (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Technology has substantially changed the accounting practice, impacting how financial information is processed, analysed, and reported. AI, RPA, and Big Data Analytics are not used very often, which could be a sign of problems that make them hard to adopt. The rankings for relevance and utilisation could demonstrate how practitioners see things rather than how people actually use them. It is necessary to understand the level of utilisation and relevancy of various types of technologies in accounting practices. The study aims to determine the current utilisation of technology in accounting practices and further outline the relevance of each technology specifically employed in both audit and non-audit firms. The current study is quantitative in nature and approached ten (10) practitioners, which consist of executives, managers, and senior management who are directly responsible for the process of preparing financial statements. The participants were requested to rank the relevance and current level of use of 17 types of technology established by the Malaysian Institute of Accountants (MIA). The findings ranked and assigned weightage to each item of technologies based on three (3) approaches. The most used and relevant technologies among audit and non-audit firms with scores over 90% are Microsoft Applications, Communication Technology, Mobile Applications, Fintech, Application Software, and Online Communication. However, the utilisation and relevancy of emerging technologies like Artificial Intelligence, XBRL, Robotic Process Automation, and Big Data Analytics remain relatively low, falling below 60%. If Weighted Cooke’s Index approach to be applied, blockchain will be assigned the highest weightage among other technologies due to its rarity and significant potential benefit to the profession. The limited number of participants and the exclusive focus on specific professionals within the accounting field might limit the applicability of the findings. Future research should investigate the actual usage of these technologies on a broad scale to validate the results that have been gathered and comprehend the factors that impact the utilisation and importance of technology in the real-world accounting profession.